Analisis Strategi Pengembangan Dalam Persaingan Lembaga Keuangan Mikro Syariah Di Aceh - Arifin, Muhammad; Aulia, Riza; Azizah, Nurul (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
In the operation of Islamic financial institutions, there must be various threats that occur, then every Islamic financial institution must have the right strategy to increase endurance and power competition. This study aims to determine the strength and weaknesses as well as opportunities and threats as well as development strategies PT LKMS Mahirah Muamalah in the midst of competition for Islamic banks in Aceh, using a qualitative descriptive method with a SWOT analysis through Interview. The results showed that there were 9 strengths, 6 weaknesses, 6 opportunities and 5 threats. From these various factors obtained 3 alternative development strategies (1) S-T Strategy, (2) Strategy S-O and (3) Business strategy with strategy implementation diversification.